Propelling efficiency of front crawl swimming - Toussaint, H. M.; Beelen, A.; Rodenburg, A.; Sargeant, A. J.; Groot, G. de; Hollander, A. P.; van Ingen Schenau, G. J. (Journal of Applied Physiology, 1988)
In this study the propelling efficiency (ep) of front crawl swimming, by use of the arms only, was calculated in four subjects. This is the ratio of the power used to overcome drag (Pd) to the total mechanical power (Po) produced including power wasted in changing the kinetic energy of masses of water.(Pk). By the use of an extended version of the system to Measure Active Drag (MAD-system) Pd was directly measured. Simultaneous measurement of O2 uptake (VO2) enabled the establishment of the relationship between the rate of the energy expenditure (Pvo2) and Po (since when swimming on the MAD-system Po = Pd). These individual relationships describing the mechanical efficiency (8-12%) were then used to estimate Po in free swimming from measurements of VO2. Because Pd was directly measured at each velocity studied by use of the MAD-system, ep could be calculated according to the equation ep = Pd/(Pd+Pk) = Pd/Po. For the 4 top class swimmers studied ep was found to range from 46 to 77%. Total efficiency, defined as the product of mechanical - and propelling efficiency, ranged from 5 to 8%.